Peran Ayah terhadap Perkembangan Bahasa Anak Usia Dini di RA AL-MUHI Koja Jakarta Utara: The Role of Fathers in Early Childhood Language Development at RA AL-MUHI Koja, North Jakarta - Ayang Saputri; Aas Siti Sholichah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Language development is an important aspect of early childhood development, influenced by the quality of interactions within the family environment. However, research on fathers' involvement in stimulating children's language development in the Raudhatul Athfal (RA) educational environment remains limited and largely focuses on mothers' roles in parenting. This study aims to analyze the role of fathers in early childhood language development through verbal interaction and quality time at RA Al-Muhi Koja, North Jakarta. The study used a qualitative approach with a case study method. The research subjects consisted of two children aged 5–6 years with different levels of father involvement. Subject selection was carried out purposively to obtain an in-depth picture of variations in children's language development in relation to father involvement in parenting. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion. The results showed that children who received active father involvement had better instruction comprehension skills, articulation clarity, communication courage, and vocabulary mastery than children with low father involvement. Conversely, minimal father involvement led to limited verbal interaction, which affected children's self-confidence and communication skills. This study confirms that father involvement, through consistent verbal communication and high-quality interactions, contributes positively to early childhood language development.